Impact of Applying the Saudi Stock Market Corporate Governance Regulation - Alquaymi, Ahmed Mohammad; Ahmed, Muhammad Sad Obaid Muhammad (The Arab Journal of Administration, 2025)
The research aims to see the impact of the application of the Corporate Governance Regulation on the financial performance of capital goods companies listed in the Saudi stock market during the period (2015-2020) by examining the relationship of corporate governance (company size, board independence, audit committee activity and government ownership ratio). The company’s financial performance is reflected in the return on assets (ROA), and the extent to which the corporate commitment to the governance regulation affects the financial performance of the company as well as the return on assets (ROA) Also, in order to achieve the research objectives, data from the companies’ financial lists and reports were collected and analyses using the software (SPSS) resulted in a relationship between corporate governance and financial performance where (There is a connection to the size of the Board of Directors) and the lack of relationship to the rest of the variables with financial performance. Research has also confirmed that corporate adherence to the Corporate Governance Regulation after mandatory application has a positive impact on financial performance. (There is a positive impact of the size of the Governing Council) on financial performance and the absence of an impact on the rest of the variables.